Climate Change Vulnerability of Livelihoods of People Residing in Kaski District of Nepal - Gajurel, Basu Dev; Devkota, Bhupendra (Journal of Hydrology and Meteorology, 2024)
This study assesses the climate change vulnerability of livelihoods across altitudinal gradients in the Kaski district of Nepal. A sample of sixty-five households from four different communities in municipalities (Annapurna rural municipality and Machhapuchchhre rural municipality) was selected through random sampling and surveyed at various elevations. The Principal Component Analysis (PCA) approach and the Composite Index Method (CIM) were employed to evaluate and determine IPCC-VI. To derive Adaptive capacity, Sensitivity, and Exposure, the components such as Social Demographic Profile (SDP), Social Networking (SN), Livelihood Strategies (LS), Health (H), Water (W), Food (F), Natural Disaster and Climate Variability (ND CV) were used. The trend of the temperature and rainfall were analyzed and it was found that the mean annual maximum temperature is increasing at a rate of 0.036°C per year and the annual rainfall is decreasing at 14.532 mm per year. Among the communities, Melache (2210m), in Annapurna Rural Municipality exhibited the highest vulnerability (IPCC-VI: 0.118), whereas Hudu (1490m) showed a lower vulnerability index (0.025). In Machhapuchchhre Rural Municipality, Dhampus upper region (1660m) displayed moderate vulnerability (IPCC-VI: 0.043), with the Dhampus lower region (1360m) showing the least vulnerability (-0.011). So, all the communities demonstrated intermediate vulnerability levels indicating a need for tailored adaptation strategies across the elevation levels. Effective adaptation efforts could improve community resilience by addressing local climate challenges, ensuring sustainable livelihoods, and reducing future vulnerability risks.